Analisis Penilaian Berorientasi Higher Order Thinking Skills siswa Kelas V - Hisyam Abdul Kholiq; Filia Prima Artharina; Prasena Arisyanto (JANACITTA, 2019)
The purpose of this study was to investigate the implementation of Higher Order Thinking Skills (HOTS) oriented assessments on the 1st theme at 1st semester of Natural Sciences (IPA) grade V students at Candi 01 Semarang Elemntary School. This research is a qualitative research with data analysis steps including data reduction, data presentation and conclusion drawing. The data presentation in this research is a descriptive text artist. The results showed that Candi 01 Semarang Elementary School had carried out the assessment in class V well according to Permendikbud No. 23 of 2016. This is evidenced by the results of the analysis that show that the questions used in daily assessment, midterm assessment and final semester assessment meet almost all assessment criteria in every aspect, but the questions used are not all included in the HOTS question category because there are questions that only measure low-level cognitive levels. The assessment carried out has fulfilled all stages starting from planning the assessment, developing the assessment instruments, carrying out the appraisal, utilizing the results of the appraisal and reporting the results of the evaluation in the form of numbers 1-100 and description.